Pengembangan Kurikulum Pendidikan Adab bagi Siswa Berbasis Kitab Al-Lubāb min Kitāb Al-Adab - Astoko, Dudi Budi; Abbas, Ngatmin (MAMBA'UL 'ULUM, 2026)
This study develops an adab education curriculum for students based on the classical text Kitab Al-Lubāb min Kitāb al-Adab. Using a qualitative library research method, the study analyzes the text’s teachings to identify core adab values and educational guidelines. The findings indicate that the book systematically covers ethical conduct across various aspects of life, including ritual practices, social interactions, and personal habits, providing a rich source for curriculum design. The analysis identifies eight key educational objectives, such as respect, spiritual awareness, social harmony, discipline, and moral character formation. Furthermore, the study outlines teaching methods suggested by the text, such as question-and-answer, discussion, storytelling, and role modeling, and proposes comprehensive evaluation strategies, including peer review, self-reflection, and behavioral assessment, to ensure students internalize these values. Overall, the proposed curriculum integrates adab values into learning goals, instructional content, pedagogy, and assessments to produce well-rounded, morally upright learners. The results imply that incorporating this classical adab framework can strengthen Islamic character education and help address the contemporary issue of moral decline in schools. This Al-Lubāb–based curriculum aligns with national educational goals, presenting a holistic approach that integrates cognitive, affective, and spiritual development in student learning.